Implementation of brute force algorithm for topology optimisation of wireless networks - Thike, Aye Min; Lupin, Sergey; Vagapov, Yuriy (ICSAE 2016 : conference program : 2016 International Conference for Students on Applied Engineering : 20-21 October 2016, Newcastle Upon Tyne, UK, 2016)
The paper discusses the topology optimisation of wireless networks using a brute force algorithm. In order to reduce the computational complexity of the algorithm the multi-thread application has been implemented to conduct the optimisation procedure. The efficiency of the algorithm was verified using an example task where topology of a wireless network has been optimised under various criteria.